Uma​ ​Ferramenta​ ​para​ ​Identificar​ ​Desvios​ ​de​ ​Linguagem​ ​na Língua​ ​Portuguesa - ​Nau​, Jonathan​; ​Haendchen​ Filho, Aluizio​; ​Passero, Guilherme​; ​Cavaco, Vinicius​ (Anais do Simpósio Brasileiro de Tecnologia da Informação e da Linguagem Humana (STIL), 2017)
The revision of formal texts is a complex task and occurs in several areas. The objective of this work is to create a tool to support the revision of texts and promote studies in automatic correction of descriptive texts. We propose a reviewer for automatic identification of language deviations in formal descriptive texts using natural language processing techniques. A case study was carried out to evaluate the proposed approach in a public set of essays. The tool identified 3,255 deviations in a universe of 762 essays.